Li-ion dual modulation in all-inorganic ZrLiO/InLiO aqueous solution-processed thin-film transistor for optoelectronic artificial synapse. (21st July 2021) - Jiang, Dongliang; Li, Jun; Li, Linkang; Fu, Wenhui; Chen, Qi; Yang, Yaohua; Zhang, Jianhua
Abstract: Implementation of brain-like neuromorphic computing systems with artificial synapses may broaden its advantages in the application field by providing devices with the characteristics of the optoelectronic response. However, all-inorganic optoelectronic synaptic devices based on solution-processed still remain largely unexplored. Therefore, ZrLiO/InLiO thin-film transistors (TFTs) based on Li-ion doping strategy are fabricated by a facile, carbon-free, and environmentally friendly aqueous solution route in this work. Li-ion is expected to play a dual modulation role in synaptic TFTs by promoting the formation of electric-double-layers and increasing the number of oxygen vacancies that can be excited by optical signals. The ZrLiO/InLiO TFT shows excellent multi-functional synaptic characteristics such as excitatory and inhibitory postsynaptic currents, paired-pulse facilitation, the transition from short-term memory to long-term memory. The optoelectronic device is sensitive to the optical signal and exhibits brain-like learning and memory abilities after repeated presynaptic stimulation. Besides, the classic biological Pavlov's dog experiments are successfully demonstrated to verify the associative learning ability of the artificial synapse. This result may provide a feasible and effective strategy for future optoelectronic neuromorphic computing devices.